Associations Between Nicotine Metabolite Ratio and Gender With Transitions in Cigarette Smoking Status and E-Cigarette Use: Findings Across Waves 1 and 2 of the Population Assessment of Tobacco and Health (PATH) Study - Verplaetse, Terril L (Nicotine Tob Res, 2020)
INTRODUCTION: Nicotine metabolite ratio (NMR), the ratio of trans 3′-hydroxycotinine to cotinine, is a biomarker of nicotine metabolism. Discrepant findings among clinical trials and population-based studies warrant replication on whether higher NMR, or faster nicotine metabolism, is associated with quitting cigarette smoking. Associations of NMR and e-cigarette use are largely unknown, as well as the relationship between NMR and gender on quitting cigarette smoking or e-cigarette use. METHODS: The Population Assessment of Tobacco and Health (PATH) Study is a nationally representative, longitudinal cohort study assessing tobacco use in the US population. In the current study, the PATH (waves 1 and 2; adult interviews) was used to evaluate longitudinal predictions in relationships among NMR and gender and their association with transitions (quit vs. current stable) in cigarette smoking status and e-cigarette use status across waves 1 and 2 of the PATH study. RESULTS: NMR and gender were not significantly associated with quit behavior for combustible cigarettes. Regarding e-cigarettes, a significant two-way interaction demonstrated that women with higher NMR were less likely to quit e-cigarette use compared to women with lower NMR (odds ratio [OR] = 0.10, 95% confidence interval [CI] = 0.02–0.57; p = .01). CONCLUSIONS: Findings identify that women with faster nicotine metabolism were 10 times less likely to quit e-cigarettes compared to women with slower nicotine metabolism across waves 1 and 2 of the PATH study. Results suggest that NMR may be used as a biomarker for transitions in e-cigarette quit behavior for women. IMPLICATIONS: Findings identify that women with faster nicotine metabolism were 10 times less likely to quit e-cigarettes compared to women with slower nicotine metabolism. Results suggest that NMR may be used as a biomarker for transitions in e-cigarette quit behavior for women. Establishing parameters for NMR collection and for the use of NMR as a biomarker for cigarette smoking behavior and e-cigarette use is an important next step, and may have implications for early intervention and treatment for cessation.